Supporting Future Career of Autistic Learners Via Technology: Design and Development of Ibakery Courseware - Shahbodin, Faaizah; Maria, Meylinda; Che Ku Mohd, Che Ku Nuraini; Jaafar, Nurul Amiera (Journal of Technical Education and Training, 2019)
The evolution of education affects the style and approach of teaching and learning. Education 4.0 as the current evolution in education focuses on the students and the usage of technology. iBakery as a form of iBook is one of the technology implementations in education for Autistic students. iBakery is an Autistic user-friendly courseware which provides a set of instructions needed in baking activity. By concentrating on the interface, content presentation, and flow of the system, iBakery could help Autistic students to learn about bakery in a fun way. From the qualitative testing which has been conducted towards target users, results show positive feedbacks on iBakery from both teachers and Autistic students. It is believed that iBakery could help Autistic students to gain their baking skills which could be applied in their future life as a chance of independent living and career opportunity.